Cultural enterprise as a tool for image building a communication plan for the promotion of UP Mindanao - Lim, Mark Jester M.
In whatever form, art has a place within the modes of social activity. Institutions, like UP Mindanao can utilize cultural enterprise for its promotion because of the following reasons: first, artistic practice and appreciation is part of the collective experience of any culture. Cultural enterprises have this ability to promote social cohesion, they can gather audiences, and they can express or represent shared norms, values, beliefs, of a society. Second, cultural enterprise can be a vehicle for communication. It must be noted that a work of art can be seen as a form of communication designed to be interpreted and experienced by persons other than its creator. Art must be seen, literature must be read, and music must be heard before any of these aesthetic products can become part of culture. Third, cultural enterprises are forms of art that mainly connects to the emotions of the public. It communicates a message by stirring emotions. In promoting UP Mindanao, the proponent realized that it is not merely communicating what is UP Mindanao as a brand or institution. It is communicating UP Mindanao Spirit to the public through the cultural enterprise. This research study utilized the constructivist and essentialist function of the cultural enterprise, especially music in expressing and shaping the way people might understand the image position of the University in the island. The core campaign plan was image positioning for the University. The researcher created an image position that highlighted the identities of UP Mindanao image and the pervasive symbol of Mindanao. Using Koro Kantahanay as a case in point, the researcher utilized the ROPE (Research, Objectives, Programming, and Evaluation) process in the public relations to create a communication plan. The proponent worked and explored on the three contributions of music to identity ? its capacity to give symbolic shape to a pre-existing or emergent identity, to contribute to the identity it feel or affective quality, and the music?s contribution to the positive valence to the UP Mindanao identity. The researcher anchored on the point that there is a popular way in engaging with the public while communicating an institution. The cultural enterprise in the University can be our communication vehicle in promoting our institution. This communication campaign is a support strategy of the existing efforts of UP Mindanao public engagements.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Speech/Corporate Communication